MENINGKATKAN KEDISIPLINAN GURU MATA PELAJARAN PADA PROSES MENGAJAR MELALUI PROGRAM PEMBINAAN KEDISIPLINAN OLEH KEPALA SEKOLAH DI SMAN 1 PSEKSU KABUPATEN LAHAT - DOSLAN DAMANIK (MANAJERIAL : Jurnal Inovasi Manajemen dan Supervisi Pendidikan, 2023)
Professional teachers will be reflected in the appearance of carrying out the dedication of tasks which are characterized by expertise in both material and methods. The expertise possessed by professional teachers is the expertise obtained through an education and training process programmed specifically for that. As a school principal, you must be able to manage time efficiently, both for your own tasks and for the school as a whole. So that complaints of teaching and learning process activities can run effectively and efficiently. The results of this study are that in the process of implementing the 1st cycle teachers are asked to take part in the teacher discipline coaching program held by the Principal. With a disciplinary coaching program, teachers' discipline increases. With the first indicator, namely the presence of an active teacher, then the second indicator, namely the activeness of the teacher in providing teaching material in accordance with the lesson plans. So the disciplinary coaching program that was held was able to increase teacher discipline in the teaching process with criteria according to the indicators as explained earlier. From the results of observations, the results of observational and interview values in cycle I, the implementation of the disciplinary coaching program can run conducively. This classroom action research was conducted in 2 cycles. This second cycle is a cycle which is a reflection of the first cycle. In cycle II, this consists of planning, observing, and reflecting on actions. In this cycle, the implementation of the disciplinary development program is also the same as that applied in cycle I, and the results of the disciplinary development program that have been implemented show an increase in the discipline of teachers at SMAN 1 Pseksu Lahat district in the teaching process. ABSTRAKGuru professional akan tercermin dalam penampilan pelaksanaan pengabdian tugas-tugas yang ditandai dengan keahlian baik dalam materi maupun metode. Keahlian yang dimiliki oleh guru profesional adalah keahlian yang diperoleh melalui suatu proses pendidikan dan pelatihan yang diprogramkan secara khusus untuk itu. Sebagai Kepala Sekolah harus mampu mengelola waktu secara efisien, baik untuk tugas-tugas sendiri maupun untuk sekolah secara keseluruhan. Sehingga keluhan  kegiatan proses belajar mengajar dapat  berjalan secara  efektif dan efisien. Hasil penelitian ini adalah pada proses pelaksanaan siklus ke-1 guru diminta untuk mengikuti program pembinaan kedisiplinan guru yang diadakan oleh Kepala Sekolah. Dengan program pembinaan kedisiplinan membuat guru semakin meningkat kedisiplinannya. Dengan indikator yang pertama yaitu Kehadiran guru yang aktif kemudian indikator ke dua yaitu Keaktifan guru memberi materi ajar sesuai dengan RPP. Maka dengan program pembinaan kedisiplinan yang di selenggarakan mampu meningkatkan kedisiplinan guru pada proses mengajar dengan kriteria sesuai indikator seperti di jelaskan sebelumnya. Dari hasil pengamatan, hasil nilai observasicdan wawancara pada siklus I, pelaksaan program pembinaan kedisiplinan dapat berjalan dengan kondusif. Penelitian tindakan kelas ini dilakukan dalam 2 siklus. siklus kedua ini adalah siklus yang merupakan refleksi dari siklus pertama. Pada siklus ke II ini terdiri dari kegiatan perencanaan, pengamatan, dan refleksi tindakan.Pada siklus ini pelaksanaan program pembinaan kedisiplinan juga sama seperti yang di terapkan pada siklus I, dan hasil dari program pembinaan kedisiplinan yang sudah di laksanakan menunjukkan peningkatan kedisiplinan guru SMAN 1 Pseksu Kabupaten Lahat pada proses mengajar .